Drain Removal Time in Pre-pectoral versus Dual Plane Prosthetic Breast Reconstruction following Nipple-sparing Mastectomy. Issue 5 (23rd May 2022) - Moriarty, Hannah K.; Baker, Nusaiba F.; Hart, Alexandra M.; Carlson, Grant W.; Losken, Albert
Abstract : Background: Pre-pectoral prosthetic breast reconstruction following nipple-sparing mastectomy (NSM) has become a popular approach compared with the dual plane technique. Our objective was to determine if there was a difference in time to postoperative breast drain removal in direct-to-implant or tissue expander reconstruction following NSM when comparing pre-pectoral with dual plane technique. Methods: A total of 200 patients (335 breasts) received NSM followed by implant or expander reconstruction at our institution between the years 2009 and 2020. Direct-to-implant reconstruction had 113 pre-pectoral versus 67 dual plane, and tissue expander reconstruction had six pre-pectoral versus 149 dual plane. Our analysis included age at mastectomy, body mass index, history of preoperative breast radiation, and smoking history. Case complications included seroma or hematoma, breast or axillary infection requiring antibiotics or operative washout, device replacement due to extrusion or infection, skin necrosis, and capsular contracture. Statistical analysis was completed with Pearson chi-square test, Fisher exact test, and the two-sample T -test using IBM SPSS Statistics 24.0 (IBM Corp., Armonk, N.Y.). Results: The average time until breast drain removal in dual plane implant patients was significantly less than in pre-pectoral implant patients (9.42 versus 14.01 days). The average time until breast drain removal in dual plane expander patients was significantly less than in pre-pectoral expander patients (11.47 versus 20.30 days). Conclusion: In both implant and expander reconstruction following NSM, patients receiving dual plane device placement had a shorter postoperative time until breast drain removal when compared with patients receiving pre-pectoral device placement.